Mapping of Ancient River Courses by Remote Sensing Techniques and Geophysical Investigation in Northern Arabian Gulf Region - Zainab Adel AL- Muturi * , Sahar Turak .Al-Mulla **, Wala′a Mageed. Al. Mosawi * ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
The Northern Arabian Gulf region is important because it have many morphological and landscape,  the most important of these  landscape  are the rivers.  So, the present study applied satellite imagery integrating with sub bottom profilers survey  to  analysis and detect  paleoachannel  courses for many  river and lagoons (Khors) in this region, includes  Khor Al-Zubair , Khor Shaitana, Khor Abdulla and Shatt Al-Arab river.Satellite imagery analysis revealed of many traces of discontinued ancient river streams such as Al-Fayeed and Al-Maʼaqel, as well as many ancient courses of presented rivers such as Euphrates, Tigris and Bahamshir. These results were confirmed by sub bottom profilers results which completed in some river channels and that revealed many buried old channels underneath the  current river bottoms. Analysis all method depicted that most ofthese water system  sites are exposed to neotectonic indicators affected on the region ingeneral.These morphotectonic activity impacted on the alteration anddiscontinuity of the river courses in the area under study.From the present study, it seems that the subsidence process  is predominant in the region, particularly in the eastern part, and  in order to reach a state of equilibrium, this was accompanied by locally uplifting sub-surface structures  in Nahr Umr, Al- Zubair, Siba, and Sanam plug sites, as well as the proposed sites between Shatt Al-Arab and Bahamshir rivers.